Effect of short carbon fiber/SiC on tribological properties of aluminium matrix hybrid composites. (1st September 2021) - Joshi, Tanmay Vivek; Mohanty, Akash
Abstract: This research study was carried out to combine the benefits of Silicon Carbide (SiC) and short carbon fiber (CF) as reinforcements in the aluminum matrix to develop the composites for automotive applications. The powder metallurgy (PM) technique was used to fabricate five samples with different compositions. Linear wear, coefficient of friction, density, and Vickers hardness of the samples were determined and compared. The sample with 6 wt.% CF and 10 wt.% SiC was found to have the optimal properties. It was observed that the linear wear was 52.32% less and the hardness was 14.58% more than the base metal.